Missile Defense: Problems and opportunities in NATO-Russia relations - Michael Paul (Stiftung Wissenschaft und Politik (SWP), 2012)
On the first day of his third term as Russian President, Vladimir W. Putin directed the Foreign Ministry to push for guarantees that US missile interceptors planned for fielding in Europe would not be aimed against Russia's nuclear facilities. A few days before at an unprecedented international conference in Moscow hosted by the Russian Ministry of Defense, the Chief of the General Staff, General Nikolai E. Makarov, repeated warnings that Russia might opt to station short-range missiles in its Kaliningrad exclave to counter the missile defense system. He added that Russia might consider a preemptive strike on the system in Europe if the situation were to worsen. Despite the NATO summit declaration of Chicago - that NATO missile defense is not directed against Russia - the dispute with Moscow goes on. Although fears of a Russian-US strategic arms race are unwarranted, concerns about Russian misperception and mistrust are not. Therefore, it is in the interest of the United States and its allies to convince Moscow that the missile defense system is not part of a larger American effort to gain strategic nuclear domination by depriving Russia of its ability to deter a nuclear attack. The best approach to overcome misperceptions would be to start cooperation by sharing information and combining capabilities
Keywords: 320